Problems of automation of fresh fruits and vegetables storage processes - Malanchuk, Yevhenii; Khrystyuk, Andriy; Sych, Vladislav (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The article contains materials for the analysis of control systems for the process of providing conditions for storage of fresh fruits and vegetables. The analysis reveals the shortcomings of existing management systems and outlines ways for further development.